Effort Reward Imbalance and its Impact on Employee General Health: An Evidence from Banking Industry - Dr. Sana Aroos Khattak; Dr. Um-e-Rubbab; Dr. Musarrat Ijaz; Aleena khan (International Journal of Business and Economic Affairs, 2022)
This study examined the predictive capability of the Effort-Reward imbalance on Employee general health through the mediating mechanism of stress. Drawing upon the postulation of social exchange theory the research studies the imbalance caused due to failed reciprocity between the effort exerted but not reciprocated in the form of rewards. Population of the study is banking sector of Pakistan. The paper also emphasizes the role of Perceived Organization support as a moderator, that can diffuse the stressful environment. Data were collected from 227 employees working in of different banks of Private sector. Results indicated that effort reward imbalance does not have a direct impact on employee general health but has a significant role in triggering stress. Stress associated with unfavorable conditions at work is related to negative effect on employee’s health. The moderating role Perceived organization support the relationship stress and employee general health was also established.